Never lose sight of enemies: giant honeybees perceive troublemakers even in mass flight mode—a case study - Kastberger, Gerald; Ebner, Martin; Hötzl, Thomas (Frontiers in Bee Science, 2025)
This case study investigates the social behavior of the giant honeybee (Apis dorsata) during mass flight activity (MFA), a critical aspect of colony functioning. This evolutionarily ancient species builds its nests on trees, cliffs, or man-made structures. A colony periodically transitions from a semi-quiescent state to MFA mode, typically up to four times a day for 5–10 min. During MFA, the colony undergoes a profound reorganization of roles, and its defense capabilities are temporarily lost as the top layer of the bee curtain peels off, making the colony less responsive to external threats. This period is thought to result in a temporary “blindness” to disturbances, increasing vulnerability. To investigate this, the study analyzes three episodes from a larger data set, each consisting of over 60,000 video frames and 4,000 infrared images, with a focus on the MFA phase. The colony was exposed to a wasp dummy designed to simulate a real threat, triggering shimmering waves when the bees were in a quiescent state. This setup allowed the study to assess how the colony's defensive readiness fluctuates during MFA. Each episode included up to 20 experimental sessions, in which the colony's responses to the wasp stimulus and the unstimulated situation were examined. Data were collected from five 11 × 11 cm quadrants on the nest surface. Thermal data were analyzed in conjunction with motion activity data from previous studies to understand the temporal and spatial dynamics of motion–heat coupling during MFA. Results show that the mouth zone of the nest acts as a command center for coordinating MFAs. Despite its temporary vulnerability during MFA, the colony can still detect and respond to external threats, although with reduced defense capabilities. This case study highlights the complex behavioral and physiological processes involved in MFA in A. dorsata and sheds light on the extent to which the colony maintains some level of defense capability despite the agitation that occurs during nest restructuring. Only for a short period of approximately 1 min is it virtually paralyzed by the external stimulation, showing signs of social thanatosis.